The Influence Of Independence, Professionalism, Individual Morality And The Effectiveness Of Internal Control On Fraud Detection - Adrian, Muhammad; Anggraini, Nia; Azzahra, Siti Bilqis Rasya; Lussianda, Erfa Okta (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2024)
Purpose – This study aims to examine and analyze the impact of independence, professionalism, individual morality, and internal control effectiveness on fraud detection. Methodology/approach – The research method employed in this study is purposive sampling. It adopts a quantitative approach. The data analysis method used in this research includes testing data quality, testing classical assumptions, testing the structural model using multiple linear regression, and hypothesis testing using IBM SPSS 22. Result – the results of the research show that (1) independence has a positive and significant effect on fraud detection, (2) professionalism has a positive and significant effect on fraud detection, (3) individual morality has no positive and insignificant effect on fraud detection, and (4) control internal has a significant positive effect on fraud detection. Keywords: Independence, Professionalism, Individual Morality, The Effectiveness Of Internal Control On Fraud Detection.